Measurement of protein non-covalent interactions in buffer and cells - Jingwen Li; Xiangfei Song; Lishan Yao (Magnetic Resonance Letters)
Nuclear magnetic resonance (NMR) serves as a powerful tool for studying both the structure and dynamics of proteins. The NOE method, alongside residual dipolar; coupling, paramagnetic effects, J-coupling, and other related techniques, has reached a level of maturity that allows for the determination of protein structures. Furthermore, NMR relaxation methods prove to be highly effective in characterizing protein dynamics across various timescales. The properties of protein systems are dictated by intra- and intermolecular interactions among atoms, which involve covalent bonds, hydrogen bonds (H-bonds), electrostatic interactions, and van der Waals forces. Multiple NMR approaches have been developed to measure noncovalent interactions, and this paper offers a concise overview of noncovalent interaction measurements using NMR, with a specific emphasis on the advancements accomplished in our laboratory.